2022
DOI: 10.2174/1389203723666220817085941
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NF-κB in Myocardial Ischemia/Reperfusion Injury

Abstract: Acute myocardial infarction (AMI ) is a threat to human life and physical health all over the world . Timely reperfusion is very important to limit infarct size and protect ischemic myocardium . Unfortunately, it also caused more severer myocardial damage, which is called "myocardial ischemia/reperfusion injury (MIRI )''. There is no effective clinical treatment for it . Over the past two decades, biological studies of NF-κB have improved the understanding of MIRI. Nuclear Factor-κB (NF-κB ) is a major transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 164 publications
0
9
0
Order By: Relevance
“…NF-κB is central to the immune response to infection ( 35 ). Incorrect regulation of NF-κB is also associated with cancer ( 36 ), inflammation ( 37 ), autoimmune ( 38 ) diseases, septic shock ( 39 ), viral infection ( 40 ), differentiation ( 41 ), apoptosis, ferroptosis ( 42 ) and cardiovascular diseases ( 43 ). NF-κB has been shown to be involved in the process of HF after ischaemia/re-perfusion ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is central to the immune response to infection ( 35 ). Incorrect regulation of NF-κB is also associated with cancer ( 36 ), inflammation ( 37 ), autoimmune ( 38 ) diseases, septic shock ( 39 ), viral infection ( 40 ), differentiation ( 41 ), apoptosis, ferroptosis ( 42 ) and cardiovascular diseases ( 43 ). NF-κB has been shown to be involved in the process of HF after ischaemia/re-perfusion ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…59 Recent studies have shown that the inhibition of NF-κB can protect against reperfusion injury. 60 Specificity protein (Sp) is composed of Sp1, Sp2, and Sp3, with Sp1 increasingly implicated in the development of atherosclerosis, including inflammation, lipid metabolism, plaque stability, and endothelial dysfunction. 61 DNA binding analyses have demonstrated that SP1 binds to the CREM promoter, leading to increased CREM expression that promotes the development of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have proven that both the NF-κB signalling pathway and SIRT1 are associated with MIRI ( Xu et al, 2021 ; Aghamohammad et al, 2022 ; Xiao et al, 2022 ). The cardiovascular protective effect of the NF-κB signalling pathway is related to regulating the inflammatory response ( Dong et al, 2022 ). SIRT1, an NAD + -dependent deacetylase, plays a significant role in antioxidative stress activity ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%